Subjectivity and Dialectic - Santibáñez - H., Guy (Revista de Psicología, 2002)
This paper analyses the most important subjective functions of the Neuroendocrine ystem from a dynamic perspective. These functions emerge from the interaction of the individuals of different species with their environments. They are phenotypic phenomena, i.e., they have a genetic basis that allows the expression of the neural framework of subjectivity; thus, the contents of the subjective processes depend on the environment or environments the individual interacts with. There is no subjectivity without a brain, and none without an environment Subjective functions - subjectivity - constitute one of the integrative functions of the brain, together with reactivity and plasticity. For a long time subjectivity was treated as a peculiar phenomenon with different denominations: mind, conscience, soul, spirit. These categories are a product of reflection, have a strong ideological significance and all refer to subjective processes. The brain has the capacity to “subjectivise” the information it receives by coding the activity of the afferent sensory channels. This consists basically in transforming the information into a virtual phenomenon directly accessible to the brain that produces it, and transmitting it to other people through introspection and language. At present, by means of recent tomographic research methods (proton emission, single photon emission, registration of magnetic activity), it is possible to establish correlations between neural activity and subjective processes. Subjectivity is a historically conditioned plastic analytic-synthetic psychological process. It is able to “produce” (images and perceptions) and “reproduce” (perceive its own perceptions) subjective phenomena in a permanent dialectical flow. It oscillates between “reality” and “phantasy”, between sensory perception and more endogenous production. it is able to generate inhibitory or excitatory stimuli that can operate on the Neuroendocrine System. Subjectivity is a psychological process that permits the operation on external and internal environments in an intentional, anticipatory, predictive and planned fashion.